Making primary school science education more practical through appropriate interactive instructional resources: A case study of Ghana - Yeboah, R.; Abonyi, U.K.; Luguterah, A.W. (Cogent Education, 2019)
This instructional resource production project explored low cost and waste materials for developing practical and interactive resources for teaching science at the basic school level. Developing countries, including Ghana, are not able to provide teachers with instructional resources for teaching and learning due to financial constraints. Science in particular is a subject that pupils and students in Ghana generally do not perform well both at the basic and senior high levels which is evident from the end of level examinations over the years. The study used exploratory and descriptive approaches under qualitative research. Convenience sampling was used to select low cost and waste materials to work with, and observation was used to collect data from the production process. The research found that waste materials can be used safely to develop appropriate and useful instructional resources that are very practical for teaching and learning of science lessons. This research projects to science teachers that they can freely turn col lected waste and low-cost materials into useful resources for effective lessons.
Research
Keywords: Primary school; science; interactive instructional resources; education